2016
DOI: 10.1080/15384047.2016.1250047
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D ligand expression in pediatric brain tumors

Abstract: Adult brain tumors establish an immunosuppressive tumor microenvironment as a modality of immune escape, with several immunotherapies designed to overcome this barrier. However, the relationship between tumor cells and immune cells in pediatric brain tumor patients is not as well-defined. In this study, we sought to determine whether the model of immune escape observed in adult brain tumors is reflected in patients with pediatric brain tumors by evaluating NKG2D ligand expression on tissue microarrays created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…21 Previous studies have demonstrated that immune infiltrate in pediatric CNS tumors has no bearing on survival. 14 Furthermore, pediatric CNS tumors may not establish an immunosuppressive microenvironment as is seen in adult CNS tumors, 13 and instead reflect a failure of immune surveillance. It is not clear, however, whether impaired immune surveillance is the result of poor lymphocyte trafficking to the tumor site or minimal expression of ligands for activating immune receptors expressed by lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Previous studies have demonstrated that immune infiltrate in pediatric CNS tumors has no bearing on survival. 14 Furthermore, pediatric CNS tumors may not establish an immunosuppressive microenvironment as is seen in adult CNS tumors, 13 and instead reflect a failure of immune surveillance. It is not clear, however, whether impaired immune surveillance is the result of poor lymphocyte trafficking to the tumor site or minimal expression of ligands for activating immune receptors expressed by lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…TMAs were constructed as previously described 13 and included triplicate cores from pediatric low-grade glioma (pLGG) (19 pilocytic astrocytoma, 4 ganglioglioma), pediatric high-grade cortical glioma (pHGG) (11 anaplastic astrocytoma, 16 GBM), DIPG (n = 9), and control (12 nontumor pediatric brain). Details can be found in the Supplementary Methods.…”
Section: Tma Construction Immunohistochemistry Staining and Image Amentioning
confidence: 99%
See 1 more Smart Citation
“…CCL3, CCL4) and absence of lymphocytes in primary tissue are consistent with the failure of DIPG-associated macrophages to trigger an effective anti-tumor immune response. Adding to the evidence for lack of an effective innate or adaptive immune response in pediatric high-grade gliomas, a previous study demonstrated the lack of NK cell infiltration into pediatric high-grade gliomas [ 16 ], although this study did not specifically investigate DIPG. An “immune cold” state of DIPG is also consistent with the lack of inflammatory cells in pediatric non-brainstem gliomas recently described [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences between mouse and human are further amplified by the presence of an ITAM signaling motif in DAP12 and a YxxM motif in DAP10 ( Figure 2B and Table 5) [214,215]. Human NKG2D ligands are expressed in ovarian cancer, leukemia, colorectal cancer and pediatric brain cancers, amongst others [216][217][218][219][220]. Regardless of ligand expression, Groh et al [221] showed that soluble MIC (sMIC) shed by tumors impaired NKG2D mediated cytotoxicity by blocking receptor engagement and thus signaling [221,222].…”
Section: Nkg2dmentioning
confidence: 99%